DESIGNING WORKED EXAMPLES TO SUPPORT MATHEMATICAL REASONING IN LEARNING CIRCLE CONCEPTS - Fitria Nengsi Puasa; Kuswari Hernawati (JME (Journal of Mathematics Education), 2026)
Students’ reliance on routine procedures and difficulties in understanding abstract geometric concepts highlight the need for instructional designs that support mathematical reasoning. This study aims to construct a worked example design framework that facilitates students’ transition from procedural understanding to mathematical reasoning in learning circles. The study employs a design and development research approach by adapting the Analysis, Design, and Development phases of the ADDIE model. the proposed worked example prototype was validated by two mathematics education experts using an expert validation sheet covering the aspects of material, construction, and language. The design integrates principles of Cognitive Load Theory and indicators of mathematical reasoning to produce a worked example prototype. The development process resulted in a worked example prototype that was validated by two mathematics education experts and deemed feasible for use after revisions. The prototype integrates Cognitive Load Theory principles and mathematical reasoning indicators to support students in recognizing patterns, formulating conjectures, and constructing logical arguments. This is achieved through an integrated presentation that minimizes extraneous cognitive load and the use of self-explanation prompts to encourage active cognitive processing. In addition, structured solution steps and paired problems are used as fading guidance to support the transition from guided learning to independent problem solving. Therefore, this study provides a worked example prototype that can serve as a reference for designing instructional materials to support mathematical reasoning in geometry learning.